Model Operet Wayang Pandawa untuk Pengenalan Bahasa Jawa pada Anak Usia Dini: Pengembangan dan Implementasi di TK ABA Karanganyar - Septika Rahmawati; Joko Pamungkas (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
Javanese, as part of local cultural identity, needs to be introduced from an early age to prevent it from being eroded by the dominance of foreign languages and digital media. One relevant approach is through traditional performing arts, packaged appropriately for children's development. This study aims to develop the puppet operetta